Prenatal diagnosis and outcomes of congenital Lower Urinary Tract Obstruction (LUTO) at Tygerberg Hospital Fetal Medicine Unit: an audit of 12 years - Bezuidenhout, Heidre (Stellenbosch : Stellenbosch University, 2021)
Thesis (MMed)--Stellenbosch University, 2015.